2017
DOI: 10.1080/02755947.2016.1269029
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Alligator Gar in a Gulf Coast River: Insights from Otolith Microchemistry and Genetic Analyses

Abstract: Growing interest in the Alligator Gar Atractosteus spatula among anglers and fishery managers has inspired efforts to better manage populations. Successful management requires identifying population structure and understanding the distribution of stocks and associated differences in life history. This is particularly important in river systems along the coast of the Gulf of Mexico, where transitions from freshwater rivers to saltwater bays provide the potential for life history diversification. We used otolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…; Daugherty et al. ). Our goal in this study was to integrate this new data into a simulation model to examine the effects of harvest on Alligator Gar populations.…”
mentioning
confidence: 98%
“…; Daugherty et al. ). Our goal in this study was to integrate this new data into a simulation model to examine the effects of harvest on Alligator Gar populations.…”
mentioning
confidence: 98%
“…Daugherty et al. () found that 90% of Alligator Gar collected with monofilament gill nets (46‐mm to 152‐mm bar mesh) were between 500 and 1,200 mm TL despite a much broader TL range of fish in the sample (113–2,040 mm). The authors attributed the resulting size distribution to gear selectivity due to the limited strength of monofilament to retain large fish (Froeschke et al.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile and adult Alligator Gar ( n = 30) were collected from San Antonio Bay using monofilament gill nets as described by Daugherty et al. (). In the Guadalupe and Trinity rivers, we collected adult Alligator Gar ( n = 296) using weighted‐effort multifilament gill nets designed to minimize size bias among adult age‐classes (Schlechte et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Daugherty et al. ). Collectively, these studies suggest that Alligator Gars of various life history stages occupy a wide range of estuarine and marine habitats.…”
mentioning
confidence: 98%